150k views
13 votes
(n-1 +7) simplify plssss helppp

User Tessie
by
5.2k points

2 Answers

12 votes

Answer: n+6

-1 + 7 = 6

So therefore, the answer is n+6

Hope this helped

User BlackJoker
by
5.3k points
9 votes

Answer:


  • \boxed{\sf{n+6}}

Explanation:

To solve this problem, first, you have to do is isolate it on one side of the equation.

(n-1+7)

First, remove parentheses.

→ n-1+7

Add the numbers from left to right.

→ -1+7=6

→ n+6

  • Therefore, the final answer is n+6.

I hope this helps you! Let me know if my answer is wrong or not.

User Qqwy
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.